The concept of solidarity within EU disaster response law A legal assessment - Romualdi, Giuliana (Alphabet, 2021)
"Over the last years, the increase of emergencies occurring within the EU - or originating outside but having repercussions on it - has progressively brought to light the need to identify a common understanding of solidarity in the EU legal order. The book provides an overview of the socalled EU disaster response law and an appraisal of its peculiarity by assessing the substantial practical and theoretical role of solidarity in shaping the main legal instruments for disaster response occurring inside the Union. Special attention is devoted to the existing instruments providing financial and in-kind assistance in the event of a disaster and to the analysis of the recent initiatives concerning the provision of assistance to face the consequences of the COVID-19 pandemic. The detailed analysis of the legal value of the solidarity clause established by Art. 222 TFEU then allows to evaluate the actual existence of solidarity obligations within EU disaster response law. Susanna Villani is Postdoctoral Research Fellow in EU Law at the Department of Political and Social Sciences of the University of Bologna. Currently, she is also Adjunct Professor of EU Internal Market and International Trade Law at the University of Bologna and member of various research teams in Italian and EU projects. In 2018, she received her PhD in EU Law at the University of Bologna in co-tutorship with the National Distance Learning University (UNED) in Spain."